Competition of marine iguana females (Amblyrhynchus cristatus) for egg-laying sites. - Rauch, N. (1988)
BIB Now: 5775
English
417
Keywords: BH, MI, EC -- Competition of marine iguana females (Amblyrhynchus cristatus) for egg-laying sites. -- Marine iguana, Amblyrhynchus cristatus, reproduction, behavior -- Iguana marina, Amblyrhynchus cristatus, reproducción, comportamiento